PERAN MORNING BRIEFING DALAM MENINGKATKAN KINERJA DAN EFEKTIVITAS KOMUNIKASI INTERNAL KARYAWAN PADA PT. AGRODANA FURURES SURABAYA - Asna Noor Fadhilah; Supriyono Supriyono (Jurnal Manajemen Pendidikan, 2026)
Morning briefing is a form of internal communication routinely implemented by companies as a medium for delivering work information, coordination, evaluation, and employee motivation. This study aims to examine in depth the role of morning briefing in improving employee performance and the effectiveness of internal communication at PT. Agrodana Futures Surabaya. This research employs a qualitative method with a descriptive approach. Data were collected through direct observation, in-depth interviews with management and employees, and documentation of company activities. The results indicate that morning briefing plays an important role in aligning employees’ work perceptions, improving work readiness, strengthening team coordination, and fostering open communication between management and employees. A well-structured and consistently implemented morning briefing also contributes to increased work discipline and better understanding of company targets. Therefore, morning briefing can be considered a strategic internal communication practice that supports organizational performance in futures brokerage companies.